Towards Green and Soft: 5G Design Considerations - Chih-Lin I; Shuangfeng Han; Zhikun Xu; Zhengang Pan (Journal of Telecommunications and the Digital Economy, 2020)
As the commercial deployment of 4G systems is picking up, technologists worldwide are beginning to search for next-generation wireless solutions to meet the anticipated demands in the 2020 era given the explosive growth of mobile Internet and the Internet of Things (IoT). This article presents our perspectives of the 5G technologies with two major themes: Green and Soft. By rethinking the Shannon theorem and traditional cell-centric design, network capacity can be significantly increased while network power consumption is steady or even decreased. The feasibility of the combination of Green and Soft is investigated through five interconnected areas of research: energy efficiency and spectral efficiency co-design, no more cells, rethinking signalling/control, invisible base stations, and full duplex radio.